Evaluating the Pilot Implementation of the DSWD Walang Gutom Program: A Case Study on Its Impact in Addressing Involuntary Hunger in Tondo - Arcinas, Carmelito C.; Jimenez, Vincent Patrick L. M.; Mitra, Lemuel Joeb N.; Paredes, Ferdinand R.; Malang, Bernandino P.; Malang, Jocelyn DS. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The Department of Social Welfare and Development (DSWD) launched the Walang Gutom (No Hunger) Program to address involuntary hunger among vulnerable populations in the Philippines. This study evaluates the pilot implementation of the program in Tondo, Manila, focusing on its impact on hunger and the lives of beneficiaries. The program com-bines direct financial assistance through an Electronic Benefit Transfer (EBT) system with social interventions like job training, nutritional workshops, and community engagement. While the program shows promise in addressing hunger and empowering beneficiaries, challenges such as eligibility criteria, limited funding, and digital literacy barriers need to be addressed. The study recommends strategies to enhance the program's effectiveness and sustainability, including strengthening out-reach efforts, improving digital literacy, and expanding the program's reach to more vulnerable communities. Evaluations of effectiveness have yielded favorable results, with notable improvements in food security observed among beneficiaries. The progress in food security for house-hold beneficiaries is encouraging, and focused interventions can further enhance these positive outcomes. Ongoing assessments allow the pro-gram to adjust to the evolving needs of participants, ensuring sustained effectiveness. Beneficiary feedback emphasizes the program’s respon-siveness and the high quality of services, indicating overall success in achieving its goals.